Fostering Diversity, Equity and Inclusion in Learning and Teaching of Digital Business and Management Education - Samuel Adeyinka-Ojo; Tek Yew Lew (Tecno Scientifica Publisher, 2026)
This paper aimed to explore the importance, benefits, and challenges of the diversity, equity, and inclusion (DEI) framework in learning and teaching (LT) within digital business and management education (DBME). DEI components were found to be indispensable for crafting sustainable, effective, and socially responsible learning and teaching spaces in business schools across major academic disciplines, including digital business, marketing, entrepreneurship, human resources, tourism, hospitality, public relations, events management, accounting, finance, international business, and general management education. A notable gap existed among academics, practitioners, and policymakers regarding the integration of DEI principles into learning and teaching environments. Specifically, the extant literature had underreported and failed to comprehensively identify the benefits of DEI in the learning and teaching of digital business and management education, as well as the challenges associated with implementing DEI within volatile, uncertain, complex, ambiguous, disruptive, and diverse (VUCAD²) learning and teaching environments. The research method adopted was the Logic of Aggressive Synthesis (LAS). The findings demonstrated both the benefits and the potential perils of implementing a DEI framework in learning and teaching within digital business and management education. Implications and directions for future research were also discussed.